The medieval economy of salvation : charity, commerce, and the rise of the hospital - Davis, Adam Jeffrey, 1973- (Cornell University Press, 2019)
"Explores the connection between the medieval commercial economy and the rise of hospitals as new charitable institutions in the Latin West"--